COMPORTAMENTO DE LINHAGENS E VARIEDADES DE FEIJÃƒO (ð˜—. ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ L.) em RelaÃ§Ã£o a ð˜Œð˜µð˜ªð˜¦ð˜ð˜ð˜¢ ð˜»ð˜ªð˜¯ð˜¤ð˜¬ð˜¦ð˜¯ð˜¦ð˜ð˜ð˜¢ TREISCHKE, 1832 - Ramalho, F. S.; Albuquerque, M. M.; Machado, R. C. R. (REVISTA DE AGRICULTURA, 2020)
COMPORTAMENTO DE LINHAGENS E VARIEDADES DE FEIJÃƒO (ð˜—. ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ L.) em RelaÃ§Ã£o a ð˜Œð˜µð˜ªð˜¦ð˜ð˜ð˜¢ ð˜»ð˜ªð˜¯ð˜¤ð˜¬ð˜¦ð˜¯ð˜¦ð˜ð˜ð˜¢ TREISCHKE, 1832